Unusual Cutaneous Reaction with Erlotinib: A Brief Report with Current Review of Management of Tyrosine Kinase Inhibitor-associated Cutaneous Toxicity - Aashita; Vikas Yadav; Pragyat Thakur; Anuja Kapoor (Journal of Radiation and Cancer Research)
Tyrosine kinase inhibitors (TKIs) have emerged as the preferred choice of treatment for various tumors as a result of better outcomes and quality of life without the debilitating side effects of cytotoxic chemotherapy. Erlotinib is a TKI against epidermal growth factor receptor that is commonly used in lung cancer and pancreatic cancer. The most common adverse effect expected is cutaneous toxicity, which occurs as acneiform rash. Here, we present a case of 71-year-old man with metastatic lung cancer who had an atypical squamous-crusted eruption with intense itching and pain on his forehead that resolved spontaneously after withholding erlotinib along with supportive care. The present case depicts unusual cutaneous toxicity with the use of TKI.